Security at home: How private securitization practices increase state and capitalist control. (September 2017) - Low, Setha
The impact of the security state is not only seen in the political and spatial restrictions on public space and the public sphere or inscribed in militarized national borders and cities, but also in the increasing penetration of the domestic and private realm of home. These securitization practices and how they work can be exposed through an ethnographic analysis of formal institutional structures as well as the affective, discursive and bodily practices that make up and regulate everyday life. Examining securitization as a scalar set of spatial practices and social processes that interlock through a desire for 'security' reveals how securitization is able to keep a political stranglehold not only on poor, homeless and marginalized people who are traditionally perceived to be at risk and the target of these controls, but also on middle-class social preferences, political actions, shared feelings, and daily movements. This paper explores five of these sociospatial securitization practices including spatial enclosure, surveillance, private governance, rules and regulations, and financialization of everyday life that constrict and then redirect middle-class home life in private housing regimes in New York City.